AGROECOLOGY-BASED AGRICULTURE TO SUPPORT SUSTAINABLE AGRICULTURE: A SYSTEMATIC LITERATURE REVIEW - Sapto Wibowo (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Agroecology-based agriculture is an approach that integrates ecological principles into agricultural systems to achieve environmental, social, and economic sustainability. This study conducted a systematic literature review of recent publications to evaluate the contribution of agroecology in supporting sustainable agriculture and to identify supporting factors and challenges in its implementation. The results of the study show that crop diversification, utilisation of local resources, maintenance of soil fertility, and natural pest control are agroecological principles that contribute significantly to ecosystem stability and agricultural productivity. On the other hand, the successful implementation of agroecology is greatly influenced by policy support, the role of farming communities, access to training, and the availability of markets for agroecological products. However, challenges such as the dominance of conventional agriculture, limited access to resources, and cultural resistance remain major obstacles. This study recommends the application of multi-stakeholder collaborative strategies to strengthen the development of agroecology as an effort to transition to a sustainable and resilient agricultural system.